Konversi Komoditas Tanaman Sebagai Pilihan Rasional : Studi di Desa Iwoi Mea Jaya Kabupaten Kolaka Timur - Aisya, Aisya; Adi Jaya, Sarlan (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This study aims to describe the reasons why farmers in Iwoi Mea Jaya Village, Aere Distric, East Kolaka Timur Regency switched from cocoa plants to corn plants and explain the result of corn cultivation on the lives of farmers in Iwoi Mea Jaya Village, this research uses a qualitative method with an etnographic approach. The technique of selecting informans is carried out purposively. The data collection technique was carried out through participatory observation( Particivation Observation) ) and in-depth interviews (In-depth interview). The data collected were then analyzed using Popkin's Rational Theory (1968). The results of the study show that conversion to corn crops provides positive results for the community's economy, increases income, and to meet daily needs and make investments. Farmers choose maize because of its easier maintenance, faster harvest cycle, and high market demand, especially for animal feed.